(3JMaI Phi GdCdHGH ajef Mce OeTb ef GdNdaGA hGdedhc hGdfhGHs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3Chd GdCQLhRI GdMeO ddg GdbOje GdOGFe ebOQ GdehJ Ydi GHf BOe s
(3BNQgG (B:s
(3jfJgi GdcJGH HCNHGQ GdCejQ YdGA GdOjf hONhd OeTb SfI SJjf hSHYeGFI hHYOg hgfG hba GdeDda QMeg Gddg hHhCg ef GdLfI ZQakG hXdGdkG s
(3CQLhRI hYdjgG TQMs
(3de jdJRe GdeDda ai GdCQLhRI JfSjb GdhdGI hGdfhGH Ydi JQJjH CReGfge Hd bO jbOe hjDNQ hjYQa GdJQJjH ef GdTQMs
(3GdfSNI eUhQI HGdahJhZQGa ef CUd eNWhWI HNRGfI HGQjSs
(3ecQQ CjVkG JMJ Qbe (B612 (3JGQjN s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdJGQjNs